Effectiveness of Foot Exercise on Ankle Brachial Index (ABI) Among Hospitalized Patients with Diabetes Mellitus - Christina Puspa Dewi; Yeni Rusyani; Dwi Puji Susanti (International Forum of Researchers and Lecturers, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disorder that is rapidly increasing globally and is associated with a high risk of peripheral arterial complications. The Ankle Brachial Index (ABI) is a simple and reliable tool for screening peripheral arterial disease, while foot exercise represents a practical, low-cost, and non-pharmacological intervention to improve peripheral perfusion. This study aimed to evaluate the effectiveness of foot exercise in improving ABI values among hospitalized patients with DM. A pre-experimental one-group pretest-posttest design was implemented with 26 purposively selected inpatients with DM. Participants performed standardized foot exercises once daily for 15 minutes over two consecutive days. ABI values were measured using a sphygmomanometer and vascular Doppler before and after the intervention, and data were analyzed using a paired t-test. The mean ABI significantly increased from 0.707 (SD = 0.031) to 0.884 (SD = 0.027) (p < 0.001), indicating a clinically meaningful improvement from moderate impairment to near-normal circulation. These results demonstrate that foot exercise is effective in improving ABI values among hospitalized DM patients. The study highlights foot exercise as a safe, simple, and non-pharmacological nursing intervention that can be recommended in inpatient care settings to improve peripheral perfusion and prevent further complications related to peripheral arterial disease. This intervention offers a promising approach to managing peripheral arterial complications in diabetic patients